Optimal spacing of levels and chimneys in underground mining - Ortiz Sánchez, Oswaldo (2016)
The different factors that influence the spacing of levels and chimneys were analyzed. Some of these factors common to all mining operations that influence the spacing of levels are: Characteristics of the mineral and the encasing rock, economic conditions and the possibility of discovering ore in depth. In the case of chimneys, the most influential factors are geological considerations, the mining method and economic aspects. The most important quantifiable specific variables were considered to be the maintenance of chutes between levels and chimneys, the cost of which increases with the time of use and the volume of material that passes through them, that is, the spacing, and also the efficiency and safety translated into incremental cost. with spacing. Combining variables, two graphs were obtained showing the spacing of levels vs. incremental cost per tonne of ore in chute maintenance and snow spacing vs. incremental cost for loss of efficiency and security. This information plus other costs allowed obtaining a graph that gives us the optimal spacing for the minimum cost of level development. Similarly spacing between chimneys was generated vs. the cost per ton of ore mined. The optimal spacing corresponds to the minimum unit cost on the corresponding curve.